Therapeutic Potential of Targeting ß-Arrestin - Bond, Richard A.; Lucero Garcia-Rojas, Emilio Y.; Hegde, Akhil; Walker, Julia K. L. (Frontiers in Pharmacology, 2019)
ß-arrestins are multifunctional proteins that modulate heptahelical 7 transmembrane receptors (7TMR), a superfamily of receptors that regulate most physiological processes. ß-arrestin modulation of 7TMR function includes termination of G protein-dependent signaling, initiation of ß-arrestin-dependent signaling, receptor trafficking to degradative or recycling pathways, receptor transactivation, transcriptional regulation and localization of second messenger regulators. The pleiotropic influence ß-arrestins exert on these receptors functionally regulates a breadth of physiological functions, and additionally, ß-arrestins are involved in the pathophysiology of numerous and wide-ranging diseases, making them prime therapeutic targets. In this review we will briefly describe the mechanisms by which ß-arrestins regulate 7TMR signaling, including the mechanisms of the cellular functions modulated by ß-arrestins and relate this to observed pathophysiological responses associated with ß-arrestins. We will focus on the role for ß-arrestins in transducing cell signaling; a pathway that is parallel to the classical G protein-coupling pathway. The existence of these 7TMR dual signaling pathways offers an immense therapeutic opportunity through selective targeting of one signaling pathway over the other. Finally, we will consider several mechanisms by which the potential of dual signaling pathway regulation can be harnessed and the implications for improved disease treatments.